FOREIGN EXPERIENCE IN TAXING INDIVIDUALS’ INCOME AND ITS ADVANTAGES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article provides a comprehensive analysis of foreign experiences in taxing individuals’ income, exemplified by the systems in the United States, Germany, Japan, Singapore, and Sweden. It examines the historical development, legislative frameworks, tax rate structures, incentives, and administrative mechanisms of these systems, evaluating their socio-economic effectiveness. The study highlights the advantages of these foreign models over Uzbekistan’s current tax system, including social justice, economic incentivization, optimization of tax burden, and transparency, substantiated with concrete examples. The article concludes with practical recommendations for improving tax policy in Uzbekistan and suggestions for adapting these experiences to local conditions.